Health education from the perspective of the periodical "Echa Zdrojowe" (1914) - Renata Anna Bednarz-Grzybek (Maria Curie-Skłodowska University, Lublin, Poland, 2020)
The low hygiene level had a negative impact on the health and quality of life in Poland at the end of the 19th and the beginning of the 20th century. The solution that could improve the current state of affairs was promoting a healthy lifestyle in the education of the young generation of Poles. In the enthusiasm for health popularizing at the turn of the century, magazine articles suggested where to go for treatment, what procedures to use and how to spend free time. This mission was implemented using the balneological periodical "Echa Zdrojowe" (1914), which published content promoting the principles of hygiene and health education in society. The values of the spa in Ciechocinek were particularly praised, active forms of recreation were promoted, and the educational role of the sport was highlighted. Thanks to press reports, social knowledge about the possibilities of holiday leisure, such as summer camps which aimed at relaxation and improving health increased.